The role of venture capital in the commercialization of cleantech companies - Shakeel, Shah Rukh; Juszczyk, Oskar (University of Primorska, 2019)
Venture Capital (VC) plays an important role in the success of their portfolio companies. Small- and medium-sized companies often struggle with the resources required to succeed in the market. vc not only helps companies with the required financing but also provides the knowledge, understanding and expertise required to excel in the market. The study explores vc non-financial value-added contributions in the commercialization of clean technologies. Cleantech is a term associated with the companies involved with technologies, products, processes or services that seek to lower the negative environmental impact by improving efficiencies, reducing waste, encouraging the use of sustainable sources and environmental protection. However, the success of companies operating in this sector, at times, becomes challenging since these technologies are often disruptive in nature, contest business-as-usual practices by inducing efficiencies in the current processes or radically transforming the existing infrastructures. This qualitative case study is based on five companies operating in the Finnish clean technology sector. Data is collected in the form of semi-structured interviews whereas within the case and cross-case analysis approach is adopted to gain a comprehensive understanding of the studied phenomena. This study delineated vc’s contribution to technology development, corporate governance, mentoring & industry expertise, recruitment, collaboration & internationalization, acquiring additional financing and certification effect. The findings of this research provide important insights for the industry specialists, managers as well as the scientists involved in this field of research.
Keywords: venture capital; non-financial value addition; clean technology; commercialization; venture capital; cleantech; enterprises; entrepreneurship; finance; small and medium-sized enterprises; risk financing; business operations; capital; fi=Markkinointi|en=Marketing|